Associação entre indicadores de atenção básica em saúde bucal e indicadores socioeconômicos e de provisão de serviços de saúde em municípios paraibanos - Medeiros, Júlia Julliêta de (2012)
Brazil is marked by great social inequality, to make necessary studies to reduce these inequities, from the perspective of promoting positive impacts on the health condition of the population. This study aimed to make a regression model able to predict how social inequalities and the provision of health services interfere with tooth loss. It is an ecological study, exploratory with 223 municipalities of the state of Paraíba, in the period from 2008 to 2011. Data were collected in information systems: DATASUS (Department data processing of SUS), IBGE (Brazilian Institute of Geography and Statistics) and Plan Regionalization of Paraíba State. First, to describe the historical series of indicators of the Primary Care, a descriptive analysis was performed for the oral health indicators of the Pact of primary care and analyzed the component s history (2008 to 2011) checking if there was a significant change during the period 2008-2011 using the Kruskal-Wallis test. Then an exploratory study with three regression models was performed: Linear Normal, Gamma and Beta to verify which model fits the outcome better. The dependent variable was the complementary indicator of primary care Pact SUS, extraction ratio in relation to individual primary dental actions. As independent variables were used socioeconomic data: Population Demographics, Macro regional of health, Human Development Index, the Gini Index, Social Exclusion Index, literacy rate, proportion of rural population and Gross Domestic Product. And data of the provision of health services: Number of Teams Family Health and Dental Center, Dental Specialties, Coverage of Family Health Strategy, proportion of basic procedures, first consultation and average supervised tooth brushing. The Beta model proved superior to the others comparing coefficient of determination (R ² = 0,97) in the exploratory study. It was observed that Paraíba has low social and economic indices, high coverage of the Family Health Strategy (98,5%) and only the indicator of the proportion of specialized procedures increased significantly in the State. In the final model, tooth loss was associated with macro regional less developed of state, 3 and 4, the less literacy rate and Gini Index, as protective factors was checked Specialties Dental Center and the proportion of basic procedures individuals (R ² = 0 , 58). The conclusion is that Paraíba needs a strategic plan that aims to reduce poverty, increase education of the population and increase the supply of other therapeutic possibilities of the tooth with the increase in the proportion of individual basic procedures and implantation of specialized dental clinics.